Functional and Stylistic Analysis of Aphorisms in the Novel “Maftei” by Myroslav Dochynets (Linguostylistic Studies, 2019)
The problem of formation and development of the individual style of a writer is topical in modern linguistic studies. The writer's individual style in the context of the national language reflects the author's individual views and world perception through the peculiar language means or their unconventional use by the author. A detailed analysis of the views of scholars laid the foundation for studying the peculiarities of the individual style of the writer Myroslav Dochynets. Fiction works of Myroslav Dochynets have not yet been the subject of detailed linguistic studies (with the exception of A.Vegesh, L.Prokopovych, R.Terebus). However, the position of the author is obviously high in the modern literary world. Myroslav Dochynets is a winner of the highest awards in literature of Ukraine – the Taras Shevchenko National Prize in Literature, prestigious award of the President of Ukraine and many others.One of the specific features of the writer’s affluent language is the use of aphorisms. The aphorisms are the linguistic units that are not accidental in the content of the work but are necessarily subordinated to a definite plan of the author.The article provides the functional and stylistic analysis of aphorisms. The emphasis is laid on the semantic and stylistic classification of the aphorisms, the peculiarities of their use in the artistic discourse, including their role and place in the linguistic picture of the world of the writer.Aphorisms of Myroslav Dochynets constitute the semantic subsystem of his linguistic creativity. They excite by the depth and imagery, by the freshness of thought in the sentences concerning such themes as homeland and native home, about life, labor, world, love, happiness and destiny, about a woman. A significant group of aphorisms reflect philosophical ideas about the essence of life and human existence.The article elucidates only certain aspects of the author's mastery of creating aphorisms. In the linguistic picture of a literary work, aphorisms are integral elements of the text and style creating units. This study does not comprise all issues of aphorism creation specificity of the prominent master of word.  Further research of them is significant at the present stage of the linguistic studies development. Key words: individual style, aphorisms, sentences, concept, ethnosemantics, discourse. ReferencesAntolohiia aforyzmiv, edited by L. P. Oleksiienko. Donetsk, 2004.Vehesh, Anastasia. Expression of the Titles of the Novels by Myroslav Dochynets. Uzhhorod university scientific bulletin. Series “Philology. Social communications”, iss. 2 (32), 2014,  pp. 8–12.Dochynets, Myroslav. Maftei. Knyha napysana sukhym perom. Mukachevo: Karpatska vezha, 2016.Zhaivoronok,  Vitalii. “Natsionalna mova ta idiolect”. Movoznavstvo, iss. 6, 1996, pp. 27–32.Yermolenko,  Svitlana. “Styl indyvidualnyi”. Ukrainska mova: entsyklopediia, edited by V. M. Rusanivskyi, and O. O. Taranenko. Kyiv, 2000, pp. 603–4.Yermolenko, Svitlana. “Svoieridnist khudozhnoho movomyslennia Yevhena Pashkovskoho”. Yermolenko, Svitlana. Movno-estetychni znaky ukrainskoi kultury. Kyiv: Instytut ukrainskoi movy NAN Ukrainy, 2009.Matsko, Liubov. «Indyvidualnyi movostyl Ivana Dracha». Filolohichni nauky: Zbirnyk naukovykh prats. Sumy: Sumskyi DPU im. A. S. Makarenka, 2008, pp. 85–92.Myroslav Dochynets – prozaik, filosof, publitsyst. miroslav–dochinets.com /?tmpl= unsupported.Potebnja, Aleksandr. “Jestetika i pojetika”. Mysl' i jazyk. Moskva, 1976.Prokopovych, Lidiia. “Verbalization of the Consept TIME in the novel “Maftey” by Miroslav Dochynets’”. Research Journal of Drohobych Ivan Franko State Pedagogical University. Series “Philology” (Linguistics), no 8, vol. 2, 2017, pp. 66–9.Radziievska, Tetiana. Komunikatyvno-prahmatychni aspekty tekstotvorennia. Doctoral Thesis Abstract. Kyiv, 1999.Rusanivskyi, Vitalii. “Znaidene slovo (Pro movu tvoriv Yu. Mushketyka)”. Movoznavstvo, no 4–5, 2000, pp. 3–7.Slovnyk ukrainskoi movy, edited by I. K. Bilodid. 11 vols. Kyiv: Naukova dumka, 1970–1980.Solohub, Nadiia. Movnyi svit Olesia Honchara. Kyiv: Naukova dumka, 1991. Stavytska, Lesia. Estetyka slova v khudozhnii literaturi  20-30 rr. XX st. (Systemno-funktsionalnyi aspekt). Doctoral Thesis Abstract. Kyiv, 1996.Statieieva, Valentyna. “Spetsyfika movostyliu Ivana Chendeia”. Linhovstylistyka: Obiekt – styl, meta – otsinka. Kyiv, 2007, pp. 288–97.Terebus, Roman. Functional load of proper names in the novels “Krynychar” and “Vichnyk” by Myroslav Dochynets. Research Journal of Drohobych Ivan Franko State Pedagogical University. Series “Philology” (Linguistics), no 8, vols. 2, 2017, pp. 110–3.Fizer, Ivan. Psykholinhvistychna teoriia literatury Oleksandra Potebni: Metakrytychne doslidzhennia. Kyiv, 1996.